Beispiel Nr: 04
$ \text{Gegeben:}\\\text{Hypotenuse} \qquad c \qquad [m] \\ \text{Kathete}\qquad b \qquad [m] \\ \\ \text{Gesucht:} \\ \text{Kathete} \qquad a \qquad [m] \\ \\ a =\sqrt{c^{2} - b^{2} }\\ \textbf{Gegeben:} \\ c=5m \qquad b=4m \qquad \\ \\ \textbf{Rechnung:} \\ a =\sqrt{c^{2} - b^{2} } \\ c=5m\\ b=4m\\ a =\sqrt{(5m)^{2} - (4m)^{2} }\\\\a=3m \\\\\\ \tiny \begin{array}{|l|} \hline c=\\ \hline 5 m \\ \hline 50 dm \\ \hline 500 cm \\ \hline 5\cdot 10^{3} mm \\ \hline 5\cdot 10^{6} \mu m \\ \hline 0,005 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline b=\\ \hline 4 m \\ \hline 40 dm \\ \hline 400 cm \\ \hline 4\cdot 10^{3} mm \\ \hline 4\cdot 10^{6} \mu m \\ \hline 0,004 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline a=\\ \hline 3 m \\ \hline 30 dm \\ \hline 300 cm \\ \hline 3\cdot 10^{3} mm \\ \hline 3\cdot 10^{6} \mu m \\ \hline 0,003 km \\ \hline \end{array}$